Influence of Drug Substance on Conduct Disorders Among Children at Manga Institution, Kisii, Kenya - Omwenga, Michael Keari (Indonesian Journal of Community Services, 2025)
The prevalence of global conduct disorder (CD) among juvenile offenders ranges from 2 to 10%, making it a significant problem. This study sought to investigate the influence of drug and substance abuse on conduct disorder among young offenders. The study used a descriptive research design. There were 250 target populations. 68 juvenile offenders were chosen as sample size using basic random and census sampling techniques. A modified CDS questionnaire and interview guide aimed at FGDS participants and key informants were used to collect primary data. Descriptive accounts were used, and SPSS was used to evaluate the qualitative data. Descriptive and inferential statistical methods were used to analyze quantitative data, and tables and figures were used to display the findings. The study's findings, the majority of participants (68.3%) were first-time offenders, and they hardly ever had symptoms of a serious conduct issue. However, there was a substantial, positive, and significant (p<0.05) association between CD and family variables (r=0.797), drug and substance misuse (r=0.906), ADHD (r=0.895) among juvenile offenders, the results also showed that conduct disorder was positively and statistically significantly impacted by the independent variables that were utilized in the study, including drugs and substance misuse.